The development of the status of Druze women in the 21st century - Faraj Falah, Janan (Frontiers in Sociology, 2023)
This article analyzes the social, personal, and religious reasons for the change in the status of Druze women in Israel. In the 1970s, the first wave of female Druze teachers began when a class intended only for women was opened. In the last 20 years, there has been a fundamental change in the status of women, followed by a change in the status of women in Israel in general. This change resulted in an increase in the percentage of female Druze students compared with male Druze students. According to data from the Israeli Central Bureau of Statistics, in 2020, 68% of all Druze B. Undergraduatestudents and 64.8% of M.A students were Druze women. This increase has affected the various professions in which Druze women work. This article will also discuss the effect of the change in the status of Druze women on Druze society in general.